2021
DOI: 10.1038/s41598-021-94022-w
|View full text |Cite
|
Sign up to set email alerts
|

Tumor microenvironment in giant cell tumor of bone: evaluation of PD-L1 expression and SIRPα infiltration after denosumab treatment

Abstract: Giant cell tumor of bone (GCTB) is an intermediate malignant bone tumor that is locally aggressive and rarely metastasizes. Denosumab, which is a receptor activator of nuclear factor kappa B ligand (RANKL) inhibitor, can be used to treat GCTB. We focused on potential immunotherapy for GCTB and investigated the tumor microenvironment of GCTB. Programmed death-ligand 1 (PD-L1) and indoleamine 2,3-dioxygenase 1 (IDO1) expression and signal-regulatory protein alpha (SIRPα), forkhead box P3 (FOXP3), and cluster of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
(67 reference statements)
1
12
0
Order By: Relevance
“…Previous studies have shown that immune cells in tumor microenvironment are able to predict GCTB prognosis. 13 In agreement with this finding, we demonstrated that most analyzed TIL subset densities significantly affected GCTB outcomes, suggesting the importance of microenvironmental immune characteristics in regulating GCTB behavior. Another major finding was that TGR was positively correlated with PD-1–positive and FoxP3-positive lymphocytes but was negatively linked with CD3 + TIL density.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies have shown that immune cells in tumor microenvironment are able to predict GCTB prognosis. 13 In agreement with this finding, we demonstrated that most analyzed TIL subset densities significantly affected GCTB outcomes, suggesting the importance of microenvironmental immune characteristics in regulating GCTB behavior. Another major finding was that TGR was positively correlated with PD-1–positive and FoxP3-positive lymphocytes but was negatively linked with CD3 + TIL density.…”
Section: Discussionsupporting
confidence: 88%
“…10,11 The recently updated eighth edition of the American Joint Committee on Cancer (AJCC) staging manual redefines the staging of spinal tumors; although more comprehensive in guiding staging, its prognostic stratification ability remains to be demonstrated. 12 Some studies have reported molecular markers associated with GCTB prognosis as well, 13 but the study of these markers is limited to the small sample size, which may offer inaccurate prognostic information. Tumor growth rate (TGR), as a new radiological parameter in the field of oncology, [14][15][16][17] is an image-based measure of tumor size over time that provides a useful complement to the Response Evaluation Criteria in Solid Tumors (RECIST) in the dynamic and quantitative assessment of tumor progression.…”
mentioning
confidence: 99%
“…Firstly, high pre-treatment levels of sSIRPα could potentially signal a poor prognosis reflecting sSIRPα constitutively released by high numbers of TAMs. This is supported by SIRPα being constitutively released by MDMs and by recent evidence linking high SIRPα expression to poor survival in sev-eral tumors [11,[21][22][23][24]. Secondly, a rise in sSIRPα levels after initiation of immunotherapy may reflect the level of immune activation achieved, and thus predict the successfulness of the treatment.…”
Section: Discussionmentioning
confidence: 89%
“…Another potential therapeutic target recently identified in GCTB is the PD-1/PD-L1 immune checkpoint. Kushlinskii et al studied levels of sPD-1/sPD-L1 in blood serum samples of GCTB patients, patients with other bone tumors and healthy controls, and found higher sPD-L1 levels in all patients with bone neoplasms compared with controls, and higher sPD-1 levels in patients with GCTB and osteosarcoma compared with controls, benign neoplasms, chondrosarcoma, and chordoma studied PD-L1 expression after denosumab and found higher expression after denosumab compared with therapy-naı ¨ve primary and recurrent GCTB, concluding that PD-L1 expression is related to shorter recurrence-free survival [21]. PD-L1 expression was associated with shorter disease-free survival, because of upregulation of CD27, CD6, and IL10 genes and downregulation of LCK and TLR8 genes, which are related to maturation of bone tissue.…”
Section: H3f3a (G34) Driver Mutations Can Facilitate Diagnosticsmentioning
confidence: 86%
“…Metovic et al studied immunohistochemical PD-L1 expression in 46 GCTB and 24 aneurysmal bone cysts (ABC) and found PD-L1 expression in 28% of GCTB and 4% in ABC [20 ▪▪ ]. Toda et al studied PD-L1 expression after denosumab and found higher expression after denosumab compared with therapy-naïve primary and recurrent GCTB, concluding that PD-L1 expression is related to shorter recurrence-free survival [21]. PD-L1 expression was associated with shorter disease-free survival, because of upregulation of CD27, CD6, and IL10 genes and downregulation of LCK and TLR8 genes, which are related to maturation of bone tissue.…”
Section: Diagnostics and Translational Researchmentioning
confidence: 99%